Isolation and characterization of latent and active polyphenoloxidase in BRS Clara (CNPUV 154-147 x Centennial seedless) and BRS Morena (Marroo seedless x Centennial seedless) seedless table grapes - Lago-Vanzela, Ellen Silva [UNESP]; Pavezzi, Fabiana Carina [UNESP]; Martin, Natalia [UNESP]; Gomes, Eleni [UNESP]; Da Silva, Roberto [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
The seedless grapes BRS Clara and BRS Morena, developed in Brazil, are currently growing in popularity due to their premium texture and taste. However, there are no reports on the polyphenoloxidase (PPO) from these cultivars. In this paper, active and latent PPO from BRS Clara and BRS Morena seedless grapes were extracted using the non-ionic detergents Triton-X-100 (active) and Triton-X-114 (latent), and their catecholase activities were characterized. The PPO extracted using Triton-X-110 exhibited maximum activities at pH 6.0 and at 25 degrees C. Above 30 degrees C, a gradual decline in activities was noted, with complete inactivation at 60 degrees C. The PPO from grapes extracted with Triton-X-114 was activated with 0.2% of the ionic detergent sodium dodecyl sulfate (SDS), and exhibited maximum activities at pH 5.5 and at 30 degrees C. It was stable until the temperature reached 60 degrees C. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: Polyphenoloxidase; Triton-X-114; Triton-X-100; Seedless grapes